2019
DOI: 10.1021/acsami.9b11146
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Imprint and Inertial Switching in Ferroelectric La:HfO2 Capacitors

Abstract: Ferroelectric (FE) HfO 2 -based thin films, which are considered as one of the most promising material systems for memory device applications, exhibit an adverse tendency for strong imprint. Manifestation of imprint is a shift of the polarization−voltage (P−V) loops along the voltage axis due to the development of an internal electric bias, which can lead to the failure of the writing and retention functions. Here, to gain insight into the mechanism of the imprint effect in La-doped HfO 2 (La:HfO 2 ) capacitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 31 publications
1
59
1
Order By: Relevance
“…Note that the polarizations measured by PUND can be underestimated due to saturated loops not being measured because of the observed increase of coercive field when using PUND technique ( Fig. S6, ESI †) due to the fluid imprint field, 30 probably caused by charge injection. On the other hand, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Note that the polarizations measured by PUND can be underestimated due to saturated loops not being measured because of the observed increase of coercive field when using PUND technique ( Fig. S6, ESI †) due to the fluid imprint field, 30 probably caused by charge injection. On the other hand, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In parallel, considerable research and development effort has focused on understanding and utilizing the ferroelectric order reported in binary oxides such as doped HfO2, which are compatible with existing CMOS processes [94,95]. Hafnia-based ferroelectrics (and other similar binary systems) exhibit robust polarization stability (albeit with large coercive fields) and the potential for multi-state function [96].…”
Section: The Rise Of Hfo 2 and Related Materialsmentioning
confidence: 99%
“…[ 5–11 ] However, there are still reliability issues for practical use, including insufficient switching endurance [ 12,13 ] and fatigue properties. [ 14–16 ] In the case of HfO 2 ‐based ferroelectric thin films, their large time‐dependent imprint [ 17–22 ] and wake‐up effect [ 16,17,23–27 ] —which distinguish them from conventional ferroelectric materials—play important roles in understanding these critical issues.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was reported that the imprint effect in a HfO 2 ‐based ferroelectric capacitor occurs during polarization retention, even at room temperature. [ 17–19,21,22 ] The time‐dependent imprint also occurs in ferroelectric‐gate field effect transistors. [ 20 ] Zacharaki et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation